Evangelización, cartografía y discurso colonial: El mapa de 1713 de la misión jesuita de Mojos - Cañeque, Alejandro (2023)
This article discusses the historical significance of a leaflet printed around 1713 by the Society of Jesus to promote the mission of Mojos, located in the northeast of present-day Bolivia. Although historians generally refer to this document as «the map of the Mojos mission», this study argues that the 1713 pamphlet is much more than a map, and can be understood as the equivalent of a typical Jesuit missionary chronicle. This is of great relevance, since the Society of Jesus always marked the consolidation of its numerous missions in the Americas with the publication of a magnum opus to publicize its evangelical efforts. In the case of Mojos, although a chronicle of the mission would never be published, the pamphlet of 1713 fulfils this function, since it is both structured in the same way as the typical Jesuit missionary chronicle, whose model had been established by José de Acosta at the end of the sixteenth century, and faithfully follows all the discursive principles that shaped the Jesuit chronicles.